2013
DOI: 10.1007/s00167-013-2812-5
|View full text |Cite
|
Sign up to set email alerts
|

Repeatability and accuracy of a non-invasive method of measuring internal and external rotation of the tibia

Abstract: Non-invasive optical tracker fixation gives improved agreement with a validated method of measurement compared with devices measuring tibial rotation by foot position. This system gives the added possibility of dynamic, weight-bearing testing in the clinically important range of 0°-30° knee flexion without the need for any limb restraint.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 56 publications
1
8
0
Order By: Relevance
“…Unfortunately, the position of the foot in internal/external rotation is not correlated with the position of the tibial tubercle. This finding matches the results of previous studies that have shown that the rotation of the foot is not an accurate measure tibial rotation [ 2 , 3 , 26 ]. This does not mean that lower leg rotation as measured by foot position is not valuable.…”
Section: Discussionsupporting
confidence: 92%
“…Unfortunately, the position of the foot in internal/external rotation is not correlated with the position of the tibial tubercle. This finding matches the results of previous studies that have shown that the rotation of the foot is not an accurate measure tibial rotation [ 2 , 3 , 26 ]. This does not mean that lower leg rotation as measured by foot position is not valuable.…”
Section: Discussionsupporting
confidence: 92%
“…Utilising standard anatomical landmarks, the computer designs a three-dimensional (3D) image of the anatomy [ 15 ]. CAOS provides dynamic and real-time assessment of femoral-tibial mechanical axis (FTMA), measurements of coronal and sagittal knee alignment offering a potential alternative to radiographs [ 16 ], tibial rotational profile [ 17 ] and knee kinematics [ 18 ].…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, proper initial tension of the graft during ACL reconstruction is crucial. Some methods and devices have been developed to measure initial graft tension, but it is di cult to apply these devices in vivo [27][28][29][30][31].…”
Section: Discussionmentioning
confidence: 99%